Awareness of Women on Reproductive Tract Infections in Ru-ral Field Practice Areas of a Medical College in Mangalore - Shruthi M Shetty; K G Kiran; Sanjeev Badiger; Vinayak J Kempaller (Medsci Publications, 2017)
Introduction: The rising consequences of Reproductive tract infections (RTIs) such as cervical cancer and infertility which affect the quality of life of women and socio-economic development of the country, proves that awareness on Reproductive Tract Infections is the need of the hour. Objectives: This study was carried out to assess the awareness of Reproductive Tract Infections in women residing in rural field practice areas of a Medical College in Mangalore. Methods: A cross-sectional study was carried out on 336 women of 15-49 years of age in two rural field practice areas of a Medical College in Mangalore. Simple random sampling was done and a pretested semi structured questionnaire, after taking written informed consent was used. Frequency, percentages were calculated and Chi Square Test was applied. Results: Of 336 women, 64% mentioned that they were aware of RTIs. The major causes of RTIs as informed were lack of personal hygiene (34.4%) and more number of sexual partners (28.5%). The major health problems stated were weakness (32.1%) and infertility (14%). 41% of the respondents were aware that both partners should be treated for reproductive tract infections. Conclusion: Steps need to be taken to educate the community on RTIs and to seek health care at the earliest, as awareness is still lacking in the community.